Meshfree simulation of dynamic brittle and quasi-brittle fracture using a local damage model based on lattice particle method - Ng, Khai Ching; Chen, Hailong; Low, Wei Chen (2024)
In this paper, the particle size-dependent issue of Lattice Particle Method (LPM) for simulating dynamic brittle and quasi-brittle fracture is addressed by coupling LPM with a local damage model based on fracture energy. The proposed model is simple and more robust than the Stress Intensity Factor (SIF)-based approach as it can model mixed-mode fracture with multiple cracks without any application-dependent tuning parameter. Numerical procedures for estimating the dissipative energy and the crack tip velocity for LPM simulation are also proposed. A series of benchmark problems involving dynamic fracture and crack branching are simulated using the proposed model. Good agreements are found against existing experimental observation and solutions from other numerical methods. Although a Cartesian-like (structured) lattice configuration is employed in the current LPM method, physically meaningful and accurate crack patterns can still be captured without any special numerical treatment.